INVESTMENT BANKING TRANSACTION’S STAKEHOLDERS UNDER VALUE-BASED MANAGEMENT - ALEKSIN, Glib; STASHCHUK, Dmytro (Herald of Khmelnytskyi National University. Economic sciences, 2024)
Investment banking transactions play a crucial role in the economic mechanism. The success of investment banking transactions in today's volatile environment can be supported through stakeholder orientation and value creation management. This paper’s aim is to identify the needs and motivations of participants in investment banking operations in the context of a value-oriented approach, focusing on investor rights protection. Paper analyzes the impact of stakeholder groups on the course of investment banking transactions. It is emphasized that satisfying the interests of client companies, investors, and regulators is key not only in the pre-M&A stage but also in the integration and development phases post-M&A. The key needs and motivations that influence stakeholder participation in investment banking transactions are highlighted. Client companies require access to capital, expertise, and the minimization of transaction costs. Investment banks facilitate capital raising and provide business management advisory services, helping to reduce costs and improve operational efficiency. Investors are focused on obtaining positive financial outcomes, the security of their investments, and the transparency of transaction conditions, which include risk reduction and the presence of property rights protection mechanisms. Regulators and market infrastructure aim for compliance with the regulatory framework, market stability, and investor rights protection, ensuring a level playing field and promoting market fairness. Effective stakeholder management is achieved through transparency, adherence to equal rules, and value-oriented management tools concentrated on advisory services, transaction cost optimization, financial communication, and regulatory compliance. The alignment of the interests of clients, investors, and regulators creates mechanisms that protect investor rights, foster market stability, and ensure long-term economic benefits for all participants. Future research prospects include studying a system of key performance indicators for the digitalization of stakeholder management processes in the context of a value-oriented approach.
Keywords: stakeholders; investment banking; value-oriented management; investor rights protection; financial communication